2016
DOI: 10.3389/fpls.2016.00203
|View full text |Cite
|
Sign up to set email alerts
|

De novo Transcriptome Assembly of Floral Buds of Pineapple and Identification of Differentially Expressed Genes in Response to Ethephon Induction

Abstract: A remarkable characteristic of pineapple is its ability to undergo floral induction in response to external ethylene stimulation. However, little information is available regarding the molecular mechanism underlying this process. In this study, the differentially expressed genes (DEGs) in plants exposed to 1.80 mL·L−1 (T1) or 2.40 mL·L−1 ethephon (T2) compared with Ct plants (control, cleaning water) were identified using RNA-seq and gene expression profiling. Illumina sequencing generated 65,825,224 high-qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 87 publications
1
18
0
Order By: Relevance
“…These results indicated that carbohydrate metabolism and plant hormone signal transduction and metabolism were commonly involved in the floral transition process induced by ethephon. Similar results have been reported previously [18]. However, more carbohydrate metabolism, plant hormone signal transduction and metabolism-associated GO terms and KEGG metabolic pathways with more DEGs were enriched in the CP-T and CP-CK comparison group than in the SC-T and SC-CK comparison group.…”
Section: More Tfs Responded To Ethephon Stimulation In Sc After Ethepsupporting
confidence: 79%
See 2 more Smart Citations
“…These results indicated that carbohydrate metabolism and plant hormone signal transduction and metabolism were commonly involved in the floral transition process induced by ethephon. Similar results have been reported previously [18]. However, more carbohydrate metabolism, plant hormone signal transduction and metabolism-associated GO terms and KEGG metabolic pathways with more DEGs were enriched in the CP-T and CP-CK comparison group than in the SC-T and SC-CK comparison group.…”
Section: More Tfs Responded To Ethephon Stimulation In Sc After Ethepsupporting
confidence: 79%
“…A higher concentration of ethephon might be perceived as one type of stress encountered by pineapple plants, which results in the increased expression of TFs after ethephon treatment [17][18]. In addition to the previously mentioned ERFs, other TFs, including MYBs, WRKYs, NACs and bHLHs, were shown to be upregulated in response to ethephon treatment.…”
Section: More Tfs Responded To Ethephon Stimulation In Sc After Ethepmentioning
confidence: 99%
See 1 more Smart Citation
“…These unigenes were used for BLASTX-algorithm based searches and annotations against the protein databases Nr, SwissPort, COG, KEGG, and GO. In total, 24,911 unigenes (34.62%) were annotated in sugar apple, which is much smaller than other fruit trees, such as pineapple (58.33%), mango (85%), and loquat (70.57%), and similar to the number annotated in manchurian walnut (39.92%) and “Bartlett” pears (32.8%) (Gong et al, 2015; Nham et al, 2015; Sherman et al, 2015; Hu et al, 2016; Liu and Fan, 2016). This indicated that the functions of a large portion of the genes of sugar apple have not yet been identified.…”
Section: Discussionmentioning
confidence: 63%
“…We obtained a comprehensive and high-quality fruit transcriptome for pineapple fruit Although extensive RNA sequencing data for pineapple exists on public repositories such as NCBI SRA, only a few of these were produced from fruit (Ong, Voo & Kumar, 2012;Ma et al, 2015;Ming et al, 2015;Chen et al, 2016;Liu & Fan, 2016;Redwan, Saidin & Vijay Kumar, 2016). No data is available for the different tissues present in the pineapple collective fruit, and this fact hinders studies of pineapple fruit development.…”
Section: Discussionmentioning
confidence: 99%